Grammatical Case in Pshdar Sub-Dialect (Raparin Journal of Humanities (RJH), 2023)
This research is entitled (Grammatical case in Pishdar Sub-Dialect). Grammatical case is one of the important syntactic features in Pishdar Sub-Dialect, case is a property of noun phrases, expressed as a result of their relationship to other parts of the sentence, which in some languages is represented by a morpheme and appears at the end of a noun phrase, indicating the role played by the noun phrase in the sentence and is known as morphological case, but in some languages ​​the morphological sign does not appear and is known as the abstract case. The concept of the abstract case is an important part of the theory of Government and binding, which Chomsky and his followers have studied. under the title of case theory. According to the theory, abstract case is a universal phenomenon and exists in every language. There is no morphological case in Central Kurdish, but it is seen in some Sub- dialects belonging to Central Kurdish, such as Pishdar, Mukri, Khoshnawti and Rawandz. In this research, the grammatical case, types and characteristics of Pishdar dialect are analyzed.